Antibacterial healing-promoting hydrogel dressing and preparation method thereof
By combining thermoelectric and photothermal effects in hydrogel dressings, using temperature difference and light-driven electric potential changes, the operability problem of forming an electric field by itself in the prior art is solved, significantly promoting wound healing and improving antibacterial effect.
Patent Information
- Application Number
- CN202410764980.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, direct external electrical stimulation has problems in operability, and it is difficult to develop a healing dressing that forms an electric field by itself, and cannot effectively promote wound healing.
An antibacterial healing promotion hydrogel dressing is designed to combine the hydrogel with the drug-loaded nanofiber membrane through thermoelectric effect, which uses temperature difference to generate potential difference and promote drug release, and combines the photothermal effect of polydopamine to enhance the electrical stimulation effect.
It realizes the formation of an electric field on its own, promotes the proliferation of wound edge cells and drug release, significantly accelerates wound healing, and improves the antibacterial effect.
Smart Images

Figure CN119113176A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to an antibacterial and healing-promoting hydrogel dressing and a preparation method thereof. Background Art
[0002] The skin is an important barrier to human tissues and organs, protecting internal organs from microbial invasion and playing an important protective role when stimulated by external factors. There is a natural electric field in the human body. Ion channels distributed on the plasma membrane of skin epithelial cells will generate a potential difference when directional transporting sodium, potassium, and chloride ions, also known as transepithelial potential. When a skin wound is formed, the transepithelial potential is short-circuited, causing the center of the wound to have more negative charge and a potential difference with the surrounding normal skin, thereby forming an endogenous lateral electric field. The direction of the electric field is from the normal skin at the edge to the center of the wound. This electric field can promote directional cell migration and proliferation, and can be sustained and stable until the wound is re-epithelialized. Based on the theory of endogenous lateral electric fields, some researchers have proposed applying exogenous lateral electric fields to promote wound healing. Studies have shown that external electrical stimulation can promote cell migration and proliferation, reduce inflammatory responses, promote angiogenesis, and accelerate skin healing. However, direct external electrical stimulation has problems in operability, and it is necessary to develop a healing-promoting dressing that can form an electric field by itself. Summary of the invention
[0003] In response to the problems in the prior art, the present invention designs an antibacterial and healing-promoting hydrogel dressing. By using a hydrogel with thermoelectric effect in combination with a drug-loaded nanofiber membrane, the hydrogel layer can generate a thermoelectric effect through temperature difference to promote the proliferation and differentiation of cells at the edge of the wound, while promoting the release of drugs from the drug-loaded nanofiber membrane layer, thereby promoting wound healing.
[0004] In order to achieve the above technical objectives, the present invention provides an antibacterial and healing-promoting hydrogel dressing, which comprises at least a hydrogel layer and a drug-loaded nanofiber membrane layer;
[0005] The hydrogel layer at least includes a carrier material and a thermocouple ion pair supply material;
[0006] The drug-loaded nanofiber membrane at least comprises a fiber membrane carrier and drug powder.
[0007] In some technical solutions of the present invention, the carrier material of the hydrogel layer is polyvinyl alcohol.
[0008] In some technical solutions of the present invention, the thermocouple ion pair supply substances are sodium sulfate and sodium sulfite. Further, the concentrations of the two substances in the hydrogel layer are equal. The substances can undergo redox reactions under the action of temperature difference to generate potential difference.
[0009] In some technical solutions of the present invention, the hydrogel layer also includes sodium chloride. The ratio of the molar concentration of sodium chloride to sodium sulfate in the hydrogel is 0-6, and specifically, 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 can be cited. The addition of sodium chloride can supplement electrons and increase the speed of electron movement, thereby further increasing the conductivity, and as the concentration of sodium chloride increases, the output voltage will also increase. In addition, the ions provided by sodium chloride will induce the aggregation and arrangement of polymer segments during the freeze-thaw cycle of polyvinyl alcohol, thereby enhancing the mechanical tensile properties of the hydrogel.
[0010] In some technical solutions of the present invention, the hydrogel layer also includes a photothermal agent.
[0011] Furthermore, the photothermal agent is polydopamine. Polydopamine has good photothermal conversion ability, increases the photothermal performance of the hydrogel, and the photothermal performance increases with the increase of the concentration of polydopamine added. After adding the photothermal agent, a temperature difference can be generated in different parts of the hydrogel through local irradiation of near-infrared light, thereby promoting the redox reaction of the substance provided by the thermocouple ion pair and generating a potential difference.
[0012] In some technical solutions of the present invention, the fiber membrane carrier is a polylactic acid-glycolic acid copolymer.
[0013] In some technical solutions of the present invention, the drug-loaded nanofiber membrane also includes gelatin, and the mass ratio of gelatin to fiber membrane carrier to gelatin is 0-0.5. The addition of gelatin can further increase the drug release rate of the drug-loaded nanofiber membrane and improve the hydrophilicity of the drug-loaded nanofiber membrane.
[0014] In some technical solutions of the present invention, the drug powder is curcumin.
[0015] In some technical solutions of the present invention, the thickness of the drug-loaded nanofiber membrane is 0.15-0.17 mm.
[0016] In some technical solutions of the present invention, the hydrogel layer has a thickness of 2-3 mm.
[0017] In some technical solutions of the present invention, the outer diameter of the hydrogel layer is larger than that of the drug-loaded nanofiber membrane.
[0018] The present invention also provides a method for preparing an antibacterial and healing-promoting hydrogel dressing, the preparation method comprising at least the following steps:
[0019] Step 1, using hexafluoroisopropanol as a solvent, adding polylactic acid-glycolic acid copolymer, gelatin, and drug powder to prepare a spinning solution;
[0020] Step 2, electrospinning the spinning solution prepared in step 1 to prepare a drug-loaded nanofiber membrane;
[0021] Step 3, using water as solvent, adding sodium chloride and a thermocouple ion pair supply material, stirring until fully dissolved, adding a photothermal reagent, and ultrasonically dispersing to obtain a mixed solution A;
[0022] Step 4, preparing a hydrogel carrier aqueous solution, adding it to the mixed solution of step 3, and stirring thoroughly to obtain a hydrogel precursor mixed solution B;
[0023] Step 5, immersing the drug-loaded nanofiber membrane prepared in step 2 into the hydrogel precursor mixture in step 4, and obtaining the antibacterial and healing-promoting hydrogel dressing after freeze-thaw cycles.
[0024] In some technical schemes of the present invention, the mass fraction of the polylactic acid-glycolic acid copolymer in the spinning solution of step 1 is 12-18%, and the mass fraction of gelatin is 0-6%; further, the mass ratio of gelatin to the polylactic acid-glycolic acid copolymer is 0.1-0.5. As the proportion of gelatin increases, since gelatin itself carries a large number of hydrophilic amino groups, hydroxyl groups and the like, as the proportion of gelatin increases, the hydrophilic properties of the nanofiber membrane increase, water molecules can more easily enter the interior of the fiber, and bring out the drug molecules with the vibration effect, thereby improving the drug release effect.
[0025] In some technical solutions of the present invention, the mass fraction of curcumin in the spinning solution in step 1 is 0.1-10%. Preferably, the mass fraction of curcumin is 0.8-1.0%.
[0026] In some technical solutions of the present invention, in the electrospinning step of step 2, the ambient temperature is adjusted to 24-26° C. and the ambient humidity is 38-42%;
[0027] In some technical schemes of the present invention, in the electrospinning step 2, a No. 22 spinning needle is selected, the spinning voltage is set to 18 kV, the receiving distance is 18 cm, and the spinning rate is 0.9-1.1 mL / h.
[0028] In some technical solutions of the present invention, the molar concentration of sodium chloride in the mixed solution A in step 3 is 0-0.6 mol / L, specifically 0 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, and more preferably 0.6 mol / L. Under the same temperature difference, the higher the molar concentration of sodium chloride, the greater the output voltage that can be obtained by the prepared hydrogel.
[0029] In some technical solutions of the present invention, the molar concentration of sodium sulfate and sodium sulfite in the mixed solution A in step 3 is 0.1 mol / L.
[0030] In some technical schemes of the present invention, the mass fraction of polydopamine in the mixed solution A of step 3 is 0-0.15%. Adding polydopamine can further increase the photothermal effect of the hydrogel. The higher the amount of polydopamine added, the better the photothermal conversion effect of the hydrogel.
[0031] In some technical solutions of the present invention, the hydrogel carrier in step 4 is polyvinyl alcohol.
[0032] In some technical schemes of the present invention, the preparation of the hydrogel precursor mixed solution B in step 4 specifically includes the following steps: adding polyvinyl alcohol to deionized water at 85-95°C and stirring to dissolve for 1.5-2.5 hours to obtain a polyvinyl alcohol aqueous solution; mixing the polyvinyl alcohol aqueous solution with the mixed solution A obtained in step 3 in equal volumes, and stirring for 25-35 minutes to obtain a hydrogel precursor mixed solution B.
[0033] In some technical solutions of the present invention, the mass concentration of the polyvinyl alcohol aqueous solution prepared in step 4 is 8-12%.
[0034] In some technical schemes of the present invention, the hydrogel precursor mixture B in step 5 is freeze-thaw cycled, with a freezing temperature of -21°C to -23°C and a freezing time of 20-22h; a thawing temperature of 24-26°C and a thawing time of 2-4h; and freeze-thaw cycles are performed 2-5 times.
[0035] The beneficial effects brought by the technical solution provided by the present invention are:
[0036] 1. The present invention prepares a drug-loaded nanofiber membrane by electrospinning, and then compounds a hydrogel with a thermoelectric effect to form a double-layer dressing. The lower layer is a drug-loaded nanofiber membrane, which can slowly release drugs at the wound; the upper layer is a hydrogel with a thermoelectric effect, which can drive the equilibrium potential change of redox ions through the temperature gradient, form a potential difference to generate electrical stimulation, promote the proliferation and differentiation of cells at the edge of the wound, and move closer to the center of the wound, thereby promoting wound healing;
[0037] 2. The present invention provides a photothermal effect for the hydrogel by further adding polydopamine into the hydrogel layer. Polydopamine can absorb light energy and convert it into heat energy under the irradiation of near-infrared light. Under local irradiation, it can increase the temperature gradient of the hydrogel and enhance the potential difference. At the same time, it can further promote drug release and achieve the effect of controlling drug release. At the same time, polydopamine can also synergize with curcumin to enhance the antibacterial effect.
[0038] 3. The composite hydrogel of the present invention can also provide a moist environment for the wound, stimulate cell proliferation, accelerate epidermal migration, and facilitate wound healing; at the same time, gelatin is introduced into the drug-loaded nanofiber membrane to increase the hydrophilicity of the drug-loaded nanofiber membrane, and composite with the hydrogel to promote water to enter the interior of the drug-loaded nanofiber membrane and drive drug release. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 A schematic structural diagram of an exemplary antibacterial and healing-promoting hydrogel dressing provided in an embodiment of the present invention;
[0041] The reference numerals represent:
[0042] 1. Hydrogel layer; 2. Drug-loaded nanofiber membrane layer.
[0043] The above drawings have shown clear embodiments of the present invention, which will be described in more detail below. These drawings and text descriptions are not intended to limit the scope of the present invention in any way, but to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0044] The following is a clear and complete description of the technical solution of the present invention in conjunction with the drawings in the present invention. The described embodiments are part of the embodiments of the present invention, but not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] 1. Preparation of antibacterial and healing-promoting hydrogel dressing
[0046] Step 1: using hexafluoroisopropanol as solvent, adding a certain proportion of polylactic acid-co-glycolic acid (PLGA), gelatin and curcumin powder to prepare a spinning solution;
[0047] Step 2: The spinning solution obtained in step 1 is subjected to electrospinning to prepare PLGA / gelatin / curcumin nanofiber membrane; the ambient temperature is adjusted to 25°C and the humidity is 40% for electrospinning; a No. 22 spinning needle is used, the spinning voltage is set to 18 kV, the receiving distance is 18 cm, and the spinning rate is 1 mL / h for electrospinning.
[0048] Step 3: Using water as solvent, add a certain amount of sodium chloride, sodium sulfate and sodium sulfite, stir until fully dissolved, then add polydopamine particles, and perform ultrasonic dispersion to obtain a mixed solution A;
[0049] Step 4: Add polyvinyl alcohol to 90°C water and stir to dissolve for 2 hours to prepare a 10% polyvinyl alcohol aqueous solution; mix the prepared polyvinyl alcohol aqueous solution with the mixed solution A in step 3 in equal volumes and stir for 30 minutes to obtain a hydrogel precursor mixed solution B;
[0050] Step 5: Soak the drug-loaded nanofiber membrane prepared in step 2 in the hydrogel precursor mixture prepared in step 4, freeze it at -22°C for 21 hours, thaw it at 25°C for 3 hours, and repeat this cycle 3 times to obtain an antibacterial and healing-promoting hydrogel dressing.
[0051] The above method is used in both Example and Comparative Example 1 to prepare antibacterial and healing-promoting hydrogel dressings, the difference being that different components are added to the hydrogel layer and the drug-loaded nanofiber membrane layer.
[0052] Comparative Example 2, compared with Example 4, differs in that only a hydrogel layer is provided, and no drug-loaded nanocellulose membrane is compounded.
[0053] The addition amounts of sodium chloride, sodium sulfate, sodium sulfite and polydopamine in the hydrogel layer in the examples and comparative examples are shown in Table 1:
[0054] Table 1 Addition amount of sodium chloride, sodium sulfate, sodium sulfite and polydopamine in the hydrogel layer
[0055] Example <![CDATA[Sodium chloride / mol·L -1 > <![CDATA[Sodium sulfate and sodium sulfite / mol·L -1 > Polydopamine / wt% Example 1 0 0.1 0 Example 2 0.2 0.1 0.05 Example 3 0.4 0.1 0.10 Example 4 0.6 0.1 0.15 Comparative Example 1 0.6 0 0 Comparative Example 2 0.6 0.1 0.15
[0056] The addition amounts of PLGA, gelatin and curcumin powder in the drug-loaded nanofiber membranes in the examples and comparative examples are shown in Table 2:
[0057] Table 2 Addition amount of PLGA, gelatin and curcumin powder in drug-loaded nanofiber membrane
[0058] Example PLGA / wt% Gelatin / wt% Curcumin powder / wt% Example 1 18 0 0.9 Example 2 16 2 0.9 Example 3 12 6 0.9 Example 4 12 6 0.9 Comparative Example 1 12 6 0.9 Comparative Example 2 0 0 0
[0059] 2. Performance Test Method
[0060] 1. Thermoelectric performance test: The same temperature difference of 20° C. was set at both ends of the hydrogel layer of the dressing prepared in Examples 1-4 and Comparative Examples 1-2 to test the output voltage, Seebeck coefficient and conductivity of the hydrogel layer.
[0061] 2. Photothermal performance test: by near-infrared laser (808nm, 1W / cm 2 ) irradiate the hydrogel layer for 1 minute and test the temperature reached by the hydrogel layer.
[0062] 3. Drug release performance test: Cut about 10 mg of fiber membrane and immerse it in a centrifuge tube containing 10 mL PBS. Place the centrifuge tube in a water bath shaker with a speed of 110 rpm and a temperature of 37°C. Take out 1 mL of solution at different time points to measure the absorbance, and add 1 mL of PBS to the centrifuge tube. According to the drug standard curve equation, the Cur cumulative release rate at the corresponding time point is obtained, and the experiment is repeated three times. The formula for calculating the cumulative drug release rate is as follows:
[0063]
[0064] Where: V is the volume of PBS (V = 10 mL);
[0065] C i is the Cur concentration of the sample at the i-th moment;
[0066] m is the theoretical loading amount of Cur in the fiber membrane.
[0067] 4. Antibacterial performance test: Staphylococcus aureus was used to conduct antibacterial tests on the samples of the embodiments and comparative examples, and each group of embodiments and comparative examples was set up with two control tests, one with illumination and the other without illumination. The illumination conditions were near-infrared laser (1 W / cm 2 ) for 10 minutes, and the no-light condition means avoiding light for 10 minutes.
[0068] 5. Wound healing test: Staphylococcus aureus was selected to establish a rat full-thickness skin defect infection model to evaluate the wound healing rate of the hydrogel. Two wounds with a diameter of 10 mm were made on both sides of the spine of the rats. The left and right sides were respectively the light group and the no-light group. Near-infrared laser (1 W / cm 2 ) for 10 minutes, and the wound healing area was recorded on days 0, 3, 7, and 14, and the wound closure rate was calculated. A blank control group was set up to compare the natural healing of the rat back without any dressing.
[0069] 3. Performance Test Results
[0070] 1. Thermoelectric performance test results
[0071] Table 3: Thermoelectric performance test data
[0072] Experimental example Output voltage / mV Seebeck coefficient / (mV / K) Conductivity / (S / m) Example 1 8.05 0.28 1.22 Example 2 12.15 0.55 1.70 Example 3 13.45 0.63 2.01 Example 4 17.05 0.90 2.58 Comparative Example 1 / / 0.5 Comparative Example 2 16.95 -0.88 2.50
[0073] As shown in Table 3, under a temperature difference of 20°C, the output voltage tested by the hydrogels of Examples 1-4 can reach 8.05-17.05 mV, the Seebeck coefficient reaches 0.28-0.90 mV / K, and the conductivity is 1.22-2.58 S / m. In addition, the thermoelectric performance test parameters of Example 4, output voltage, Seebeck coefficient, and conductivity are all the highest values among Examples 1-4, indicating that when the concentration of redox ion pairs is constant, the addition of sodium chloride improves the output voltage, Seebeck coefficient, and conductivity.
[0074] 2. Photothermal performance test results
[0075] Table 4: Photothermal performance test data
[0076] Experimental example Initial temperature / ℃ Light 2s temperature / ℃ Temperature 10s after illumination / ℃ Temperature 60s after illumination / ℃ Example 1 28 30 30 30 Example 2 28 35 37 40 Example 3 28 38 42 47.5 Example 4 28 42 51 56 Comparative Example 1 28 29 29 29 Comparative Example 2 28 40 49 54
[0077] As shown in Table 4, by comparing Examples 1-4, it can be seen that in Example 1, no polydopamine was added, and basically no photothermal effect was observed, while in Examples 2-4, with the addition of polydopamine, the temperature can reach 39-47°C 60s after illumination, indicating that polydopamine has good photothermal conversion ability, and the higher the concentration, the better the photothermal performance.
[0078] 3. Drug release test results:
[0079] Table 5 Drug release rate test results
[0080] Experimental example Drug release rate / % Example 1 10 Example 2 40 Example 3 54 Example 4 56 Comparative Example 1 53 Comparative Example 2 /
[0081] As shown in Table 5, the drug release rates of Examples 1-4 can reach 10-56%, and after gelatin is added to Examples 2-4, the hydrophilicity of the drug-loaded fiber membrane is increased, and the drug release efficiency is significantly increased.
[0082] 4. Antibacterial performance test
[0083] Table 6 Antibacterial performance test data
[0084]
[0085] As shown in Table 6, the antibacterial properties of the dressings prepared in Examples 1-4 are significantly better than those of the comparative example, among which Example 4 has the best antibacterial effect, with an antibacterial rate of 98.6% under light conditions and 47.3% under no light conditions.
[0086] 5. Wound healing test:
[0087] Table 7 Wound healing rate of experimental examples
[0088]
[0089] As can be seen from Table 7, the wound healing rates of the dressings of Examples 1-4 are significantly higher than the comparative data, indicating that the technical solutions of Examples 1-4 can promote wound healing. Comparing Examples 2-4 with Example 1, after adding polydopamine, the wound healing rate under light conditions is significantly improved compared with no light conditions.
[0090] Finally, a few points should be explained: Although the present invention has been described in detail above with general descriptions and specific embodiments, on the basis of the present invention, the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that: it is still possible to modify the technical solutions recorded in the aforementioned embodiments, or to replace part or all of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. An antibacterial and healing-promoting hydrogel dressing, It is characterized in that The dressing comprises at least a hydrogel layer and a drug-loaded nanofiber membrane layer; the hydrogel layer comprises at least a carrier substance and a thermocouple ion pair supply substance; and the drug-loaded nanofiber membrane comprises at least a fiber membrane carrier and drug powder.
2. The antibacterial and healing-promoting hydrogel dressing according to claim 1, It is characterized in that The hydrogel layer also includes sodium chloride; the hydrogel layer also includes a photothermal agent, and the photothermal agent is polydopamine.
3. The antibacterial and healing-promoting hydrogel dressing according to claim 1, It is characterized in that The drug-loaded nanofiber membrane also includes gelatin, and the mass ratio of the gelatin to the fiber membrane carrier is 0-0.
5.
4. The antibacterial and healing-promoting hydrogel dressing according to claim 1, It is characterized in that The thickness of the drug-loaded nanofiber membrane is 0.15-0.17 mm, and the thickness of the hydrogel layer is 2-3 mm.
5. A method for preparing the antibacterial and healing-promoting hydrogel dressing as claimed in claim 1, It is characterized in that The preparation method comprises at least the following steps: Step 1, using hexafluoroisopropanol as solvent, adding fiber membrane carrier material, gelatin, and drug powder to prepare a spinning solution; Step 2, electrospinning the spinning solution prepared in step 1 to prepare a drug-loaded nanofiber membrane; Step 3, using water as solvent, adding sodium chloride and a thermocouple ion pair supply material, stirring until fully dissolved, adding a photothermal reagent, and ultrasonically dispersing to obtain a mixed solution A; Step 4, preparing a hydrogel carrier aqueous solution, adding it to the mixed solution of step 3, and stirring thoroughly to obtain a hydrogel precursor mixed solution B; Step 5, immersing the drug-loaded nanofiber membrane prepared in step 2 into the hydrogel precursor mixture in step 4, and obtaining the antibacterial and healing-promoting hydrogel dressing after freeze-thaw cycles.
6. The method for preparing the antibacterial and healing-promoting hydrogel dressing according to claim 5, It is characterized in that The fiber membrane carrier material in the spinning solution of step 1 is polylactic acid-glycolic acid copolymer; the mass fraction of the polylactic acid-glycolic acid copolymer is 12-18%; the mass fraction of the gelatin is 0-6%.
7. The method for preparing the antibacterial and healing-promoting hydrogel dressing according to claim 5, It is characterized in that In the electrospinning step of step 2, the ambient temperature is adjusted to 24-26° C. and the ambient humidity is 38-42%. A No. 22 spinning needle is selected, the spinning voltage is set to 18 kV, the receiving distance is 18 cm, and the spinning rate is 0.9-1.1 mL / h.
8. The method for preparing the antibacterial and healing-promoting hydrogel dressing according to claim 5, It is characterized in that In step 3, the molar concentration of sodium chloride is 0-0.6 mol / L, and the molar concentration of sodium sulfate and sodium sulfite is 0.1 mol / L.
9. The method for preparing the antibacterial and healing-promoting hydrogel dressing according to claim 5, It is characterized in that In step 4, the hydrogel carrier is polyvinyl alcohol, and the preparation of the hydrogel precursor mixed solution B specifically includes the following steps: adding polyvinyl alcohol to deionized water at 85-95° C. and stirring and dissolving for 1.5-2.5 hours to obtain a polyvinyl alcohol aqueous solution; mixing the polyvinyl alcohol aqueous solution with the mixed solution A obtained in step 3 in equal volumes, and stirring for 25-35 minutes to obtain a hydrogel precursor mixed solution B.
10. The method for preparing the antibacterial and healing-promoting hydrogel dressing according to claim 5, It is characterized in that In step 5, the hydrogel precursor mixture B is subjected to freeze-thaw cycles, with a freezing temperature of -21°C to -23°C and a freezing time of 20-22 hours; a thawing temperature of 24-26°C and a thawing time of 2-4 hours; and the freeze-thaw cycles are repeated 2-5 times.
Citation Information
Cited By
Microwave-responsive antibacterial-promoting-repairing bismuth telluride-based thermoelectric material, preparation and application thereof
CN121337986B
